Analysis of the impact of sustainability education carried out by Qatar to improve its image as a future world education goal - Muhammad Adi Sukma Nalendra (Inclusive Society and Sustainability Studies, 2021)
This article seeks to explain the role of the presence of various world-class educational institutions in Qatar which is a concrete step for Qatar in development, social and cultural by Qatar. Qatar believes that education is a major way and has a strong influence to increase Qatar's inclusiveness in the world so that it can maintain a good investment climate. This research is a conceptual paper where the data presented in this study comes from literature studies from Emerald, Science Direct, and Google Schoolar where 314 articles were found which were selected and narrowed down to find 18 articles that were most suitable from the title, abstract, to useful results. This paper also conducted simple SWOT analysis in order to mapping the strategy and provide a valid explanation in this study. From the results of the agreement in this paper, it can be found that as a socio-economic effort which is a long-term plan, education is not the only step that is achieved, but also utilizes mass media and various other aspects.